Vertically aligned carbon nanotubes synthesized from waste cooking palm oil - Suriani, A.B.; Nor, R.M.; Rusop, M. (2010)
For the first time, vertically aligned carbon nanotubes (VACNT) were produced using waste cooking palm oil as green starting materials. The synthesis was carried out in a floating-catalyst thermal chemical vapor deposition reactor. Field emission scanning electron microscopy, energy dispersive X-ray, micro-Raman and thermogravimetric analyses, showed that the carbon nanotubes are of excellent quality, comparable to those obtained using conventional carbon sources. Under a typical synthesis condition of 5.33 wt ferrocence as catalyst and a furnace temperature of 750 degrees C, a mixture of single and multi-walled carbon nanotubes of 85 purity, vertically aligned on a silicon substrate, were produced. Field emission from the VACNT indicated reasonable turn-on field at 2.25 V/mu m which corresponded to the current density of 10 mu A/cm(2). The threshold field was observed to be about 3.00 V/mu m at 1 mA/cm(2). The maximum current density of 6 mA/cm(2) measured was obtained for 4 V/mu m. It is concluded that the VACNT from the reuse of waste material are suitable for applications in flat panel displays and flat lamps. (C) 2010 The Ceramic Society of Japan. All rights reserved.